Основні особливості оптимізації показників якості розмірів координованих отворів при різних видах обробки - Бурдейна, Вікторія Михайлівна; Артюх, Світлана Миколаївна (НТУ "ХПІ", 2018)
Визначена функціональна залежність розмірів полів розсіювання від бази і позиційних відхилення осей з урахуванням питомих факторів. Розглянуто запропоновані залежності для визначення полів розсіювання розміру від бази і позиційного відхилення при обробці отворів в системах без спрямування ріжучого інструменту. Розглянуті статистичні характеристики розподілу процесу обробки отворів свердлінням в системах без спрямування від базової поверхні до осі отвору і розташування осей отворів. Запропоновані нормативні данні для розробки проекту стандарту забезпечення якості взаємозамінності розмірів координованих отворів.

The functional dependence of the size of the scattering fields on the basis and the positional deviations of the axes, taking into account the specific factors, is determined. The proposed dependences are considered for determining the fields of dispersion of size from the base and the positional deviation in the processing of openings in systems without the direction of the cutting tool. The statistical characteristics of the distribution of the process of hole drilling in systems without reference from the base surface to the axis of the opening and the location of the axes of the holes are considered. Proposed regulatory data for the development of a draft standard for quality assurance of interchangeability of the sizes of coordinated holes. For the visibility of the quality of ensuring the accuracy of coordinated holes, using the proposed dependencies, graphs of the change of scattering fields are constructed, taking into account the dependence on the elements of the instrument's tooling. The fields of dispersion of small diameter aperture processing are presented taking into account such factors as the diameters of the cutting tool, the length of the tool departure and for different hardness of the material in the form of tables to fully reflect the quality of the normative provision of production at the design stage. The tables with the reference material have been constructed to ensure the quality of the interchangeability of the coordinated holes and the main design standard. The change in diameters does not lead to a significant increase in stray field.
The main features of optimizing the sizes of coordinated holes for different types of processing
Keywords: відхилення; взаємозамінність; ріжучий інструмент; поле розсіювання; свердління; deviation; characteristic; interchangeability